2016
DOI: 10.1097/ccm.0000000000001647
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Origin and Risk of Neonatal and Maternal ICU Admission*

Abstract: Women from Africa and the Caribbean and, in particular, Ghana and Jamaica, are at higher risk of admission to ICU around the time of delivery, as are their newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The overall rate of admission to intensive care during pregnancy and the postnatal period was similar to that reported in other international studies (2–4:1000) 16,36 . Studies from the Netherlands, 16 Canada, 17 and the USA, 18 conducted in local populations, similarly show an association between Black ethnicity or African or Caribbean origin and admissions to intensive care in pregnancy and the postpartum period. In common with other studies examining severe maternal morbidity in the UK we found no association with socio‐economic grouping, reflective of the universal healthcare system 37 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The overall rate of admission to intensive care during pregnancy and the postnatal period was similar to that reported in other international studies (2–4:1000) 16,36 . Studies from the Netherlands, 16 Canada, 17 and the USA, 18 conducted in local populations, similarly show an association between Black ethnicity or African or Caribbean origin and admissions to intensive care in pregnancy and the postpartum period. In common with other studies examining severe maternal morbidity in the UK we found no association with socio‐economic grouping, reflective of the universal healthcare system 37 …”
Section: Discussionsupporting
confidence: 86%
“…It is unclear to what extent this observed association is explained by differences between ethnic groups in demographic, lifestyle, pregnancy and birth factors, including co‐morbidities such as gestational diabetes and hypertension, which are more common in women of ethnic minority backgrounds 14,15 . The extent to which intensive care admissions in pregnancy and birth vary by country of origin has been examined in cohorts from the Netherlands 16 and Canada; 17 in both countries, migrant women were more likely to have admissions to intensive care. Variation by ethnic group has been examined in the USA, 18 where Black women are more likely to be admitted.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we included socioeconomic factors in propensity score matching, such as income quintile and maternal country of origin, which also strongly predict severe maternal morbidity. 20,21 Our study included only 1 randomly selected delivery per woman, thereby avoiding any potential overestimation of the risk of infertility treatment in repeat pregnancies. 12 Another small single-centre study also showed an increased risk of severe maternal morbidity related to infertility treatment (OR 2.40, 95% CI 1.10-5.23).…”
Section: Discussionmentioning
confidence: 99%
“…In our centre, immigrant women had greater odds of poor neonatal outcomes, including abnormal CTG results, CS due to abnormal CTG results and Apgar scores at 5 min. A large study conducted in Canada that included more than 800,000 births showed that the rate of neonatal ICU admissions was higher among infants born to immigrants from South Asia, Africa and the Caribbean than the infants of native Canadian mothers (RR 1.41 CI 95%, 1.36 to 1.46) [ 20 ]. Newborns admitted to the ICU may be at increased risk of neonatal mortality and have a significantly higher probability of long-term morbidity [ 21 ].…”
Section: Discussionmentioning
confidence: 99%